Upaya Peningkatan Perekonomian Masyarakat di Desa Sumbersekar melalui Optimalisasi Potensi Desa - Al Banna, M.Ulil Azmi; Apriliani , Priska; Sitari, Mayang; Bakhtiar, Ary; Ramadhani, Festy Putri (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2025)
Purpose – The aim of this activity is to improve the community's economy by utilizing the potential of Sumbersekar Village by processing low grade orange fruit into products with high selling value. Design/methodology/approach – The methods used in implementing this activity include obtaining permits, interviews, data collection, problem identification, program preparation, counseling and delivering material, mentoring, monitoring and evaluation, as well as reporting and publication. Findings – Through this activity, output can be produced in the form of a product resulting from the use of orange fruit with a low grade of eco-enzyme liquid which has been proven to be able to change waste which was previously worthless into a product with high selling value. Apart from that, making sponge cake with the addition of orange juice has succeeded in creating new innovations that support re- branding of local MSME sponge products, as well as increasing the community's knowledge and ability in processing and diversifying products from citrus fruit, so that the community is able to carry out production independently after this activity is completed. This can improve the community's economy along with the number of existing orders. Originality/value – Through activities carried out by PPK ORMAWA HIMAGRI UMM, the people of Sumbersekar Village are able to process low grade orange fruit into products that are diverse and have selling value, so that Sumbersekar Village can become an entrepreneurial village that is not only superior in its resource potential but also in the diversity of its products. processing.